On Age, Authenticity, and the Ageing Subject - Gilleard, Chris (International journal of ageing and later life : IJAL, 2022)
This paper is concerned with the relationship between selves as subject positions and the experience of aging. The existing psychological literature on “subjective” and “objective” age, it argues, has failed fully to engage with the idea of subjectivity, focusing instead upon what are ascribed and attributed identities. In contrast to treating age and ageing as some object-like characteristic potentially applicable to both things and persons, this inquiry explores the internal experience of ageing and whether such experience can realise an authentic subject position. In begins with an outline of De Beauvoir’s views of the “unrealisability” of such a subject position and proceeds to consider whether her views are the necessary consequence of the phenomenological existentialism of Sartre and Heidegger that frames her thesis. Such foreclosure on De Beauvoir’s part, I conclude, is not inevitable, and, ultimately, there is a choice between what may be termed a Sartrean or a De Beauvoir position on the possibility of realising an authentic subjectivity of age.